2021
DOI: 10.3177/jnsv.67.84
|View full text |Cite
|
Sign up to set email alerts
|

Early 1,25-Dihydroxyvitamin D<sub>3</sub> Supplementation Effectively Lowers the Incidence of Type 2 Diabetes Mellitus via Ameliorating Inflammation In KK-A<sup>y</sup> Mice

Abstract: Few studies have been performed to investigate the effect of vitamin D supplementation and T2DM in type 2 diabetic animal models. The present study aimed to explore the relationship between early 1,25-dihydroxyvitamin D3 [1,25(OH)2D3] and the incidence of T2DM and determine whether early 1,25(OH)2D3 supplementation was associated with inflammation in KK-A y mice. The KK-A y mice were divided into 4 vitamin D treatment groups, the low-dose vitamin D supplementation group (VDS-L, 1.5 mg/kg 1,25(OH)2D3), moderate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 42 publications
1
2
0
Order By: Relevance
“…Thus, weight loss interventions play a crucial part in the management of T2DM. Consistent with a previous study [32], our results showed that 1,25(OH) 2 D 3 treatment reduced the fasting blood glucose and insulin levels and ameliorated glucose tolerance and insulin sensitivity. Dyslipidemia is a prevalent comorbidity of T2DM, which is marked by augmented serum TG, TC, and LDL-C levels, and/or lowered HDL-C levels [36].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Thus, weight loss interventions play a crucial part in the management of T2DM. Consistent with a previous study [32], our results showed that 1,25(OH) 2 D 3 treatment reduced the fasting blood glucose and insulin levels and ameliorated glucose tolerance and insulin sensitivity. Dyslipidemia is a prevalent comorbidity of T2DM, which is marked by augmented serum TG, TC, and LDL-C levels, and/or lowered HDL-C levels [36].…”
Section: Discussionsupporting
confidence: 93%
“…T2DM is a multi-factor metabolic disorder with growing incidence worldwide [31]. Previous clinical and basic studies indicated that vitamin D might exert beneficial effects on the symptoms or the prevention of T2DM [14,16,17,32]. Furthermore, a latest metaanalysis suggested the beneficial effects of vitamin D on the con- trol of blood glucose in patients with T2DM and the prevention of diabetic complications [33].…”
Section: Discussionmentioning
confidence: 99%
“… 17 Early vitamin D supplementation reduced the incidence of T2DM by improving inflammation in KK-Ay mice. 18 Early detection of vitamin D deficiency can be an important factor in preventing T2DM. In addition, the timely detection of vitamin D deficiency and supplementation in people who already have diabetes may be beneficial in improving insulin resistance, maintaining blood glucose homeostasis, and reducing the risk of complications.…”
Section: Discussionmentioning
confidence: 99%